Optimizing milpa agrosystems with beneficial microbes and their ecological interactions: a review - Blanca Rojas-Sánchez; Sergio de los Santos-Villalobos; Juan J. Valdez Alarcón; Ana T. Chávez-Bárcenas; Ma. del Carmen Orozco-Mosqueda; Gustavo Santoyo (Discover Applied Sciences)
Abstract Ensuring food security through sustainable systems remains a key goal for the agricultural sector. However, poor crop management practices in recent decades have caused significant ecological harm, evidenced by climate change impacts, soil degradation, and water scarcity. Biotic and abiotic stresses during crop development further reduce yield and quality. Reviving traditional farming practices, such as the milpa system, offers a solution to boost production sustainably while repairing past damage. This comprehensive polyculture system centers on maize, intercropped with beans, squash, chili, fava beans, and other crops. Ecologically, milpas enhance biodiversity, improve soil physicochemical properties, and mitigate environmental harm through beneficial interactions among plants, insects, and microorganisms. This work examines these interactions, with a focus on the role of beneficial microorganisms in reversing environmental damage and revitalizing milpa systems. Adopting these tools can strengthen traditional practices, promoting sustainability and ensuring food security.